The impact of ergonomic design on smart garments - Boldt, Rachel S. (2020)
This paper reports the design process of a smart garment, which comprised 3-lead sEMG (Surface Electromyography) electrodes. The ergonomic design is central for a proper monitoring response because it is a related with the stability and very well contacted between the electrode and the user’ body. For this, different body postures and the t-shirt behavior on the body was studied and simulated using a virtual prototype. This approach contributed to understanding ways to solving problems related to fit and the electrodes’ stabilization. Furthermore, physical and electronic tests using a prototype on a human subject were conducted. The real prototype presented positive results on the EMG monitoring, showing the impact of ergonomic design on the smart garment. The EMG system was tested and presented good results, especially in regular movements. However, the system still needs to be improved in order to get a better signal when it comes to movements without pauses.